2008
DOI: 10.1002/ijc.23480
|View full text |Cite|
|
Sign up to set email alerts
|

Estrogen‐mediated downregulation of CD24 in breast cancer cells

Abstract: We have previously reported on the relevance of the prevalence of CD44 1 /CD24 2/low cells in primary breast tumors. To study regulation of CD24, we queried a number of publicly available expression array studies in breast cancer cells and found that CD24 was downregulated upon estrogen treatment. We confirmed this estrogen-mediated repression of CD24 mRNA by quantitative realtime PCR in MCF7, T47D and ZR75-1 cells. Repression was also seen at the protein level as measured by flow cytometry. CD24 was not downr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 34 publications
2
28
1
1
Order By: Relevance
“…The siRNAs used were as follows: siGENOME nontargeting siRNA 2, ER␣, HDACs 1 to 10 (Dharmacon), and FoxA1 (4). NCoR, SMRT, LCoR, and NRIP1 siRNA experiments were performed as described previously (31).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The siRNAs used were as follows: siGENOME nontargeting siRNA 2, ER␣, HDACs 1 to 10 (Dharmacon), and FoxA1 (4). NCoR, SMRT, LCoR, and NRIP1 siRNA experiments were performed as described previously (31).…”
Section: Methodsmentioning
confidence: 99%
“…For example, gene expression profiling has demonstrated that greater than 50% of ER␣ target genes are downregulated upon E2 treatment in MCF7 breast cancer cells as well as in breast tumors (5,8,16,53). We (31,54) and others (1,3,19,21,52,58,59,65,70) have shown that critical genes like those coding for CD24, E-cadherin, BASE, interleukin-6 (IL-6), IR, retinoblastoma protein (Rb), ERBB2, vascular endothelial growth factor (VEGF), tumor necrosis factor alpha (TNF-␣), and CD36 are repressed by E2. Many of these E2-repressed genes are cell cycle inhibitors like cyclin G2 (CCNG2) (66), proapoptotic genes, or tumor suppressor genes, and thus their repression could be a critical step in augmenting the growth and survival of a tumor and thereby in the development and/or progression of breast cancer.…”
mentioning
confidence: 96%
“…These markers are crucial for the identification and isolation of CSCs. Another biomarker, CD24, a heavily glycosylated mucin-like cell surface protein, is expressed in many human malignancies including lymphomas, 19 small cell and non-small cell lung carcinomas, 20 nasopharyngeal carcinomas, 21 breast cancers, 22 clear cell renal carcinomas 23 and hepatocellular carcinomas. 24 Recently, Irene Oi Lin Ng, of Hong Kong University, noted that CD24 is upregulated in chemoresistant and recurrent HCC patients and that it is an important biomarker for hepatic CSCs.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it has been suggested that estrogen/ER· functionally regulates putative breast cancer stem cells because CD24 is repressed by estrogen. and this repression is a direct transcriptional effect depending on ER· and histone deacetylases (HDACs), while CD44 is up-regulated by estrogenbound ER· (11,32,33). It is interesting to note that metformininduced down-regulation of CD24 was accompanied by a significant up-regulation of CD44, thus suggesting that a CD24/CD44 cross-talk could take place also in ER·-negative breast cancer cells; obviously, it should involve other yet to be explored estrogen/ER·-independent regulatory mechanisms such as epigenetic silencing or involvement of other transcription factors.…”
Section: Discussionmentioning
confidence: 99%